Clinical evaluation of 3D printed nano-porous hydroxyapatite bone graft for alveolar ridge preservation: A randomized controlled trial - Pennapa Kijartorn; Jirapa Wongpairojpanich; Faungchat Thammarakcharoen; Jintamai Suwanprateeb; Borvornwut Buranawat (Elsevier, 2022)
Background/purpose: Ridge resorption after tooth extraction may result in inadequate bone volume and unfavorable ridge architecture for ideal implant placement. The use of bone substitutes has been advocated to fill extraction sites and to enhance primary implant stability. This study was made to evaluate the clinical efficacy of novel 3D printed nano-porous hydroxyapatite (3DP HA, test group) in comparison to nano-crystalline bone graft (NanoBone®, control group) in alveolar ridge preservation prior to implant placement. Materials and methods: Thirty patients were randomized into two groups following tooth extraction. All extracted sockets were filled with 3DP HA or NanoBone® and covered with a non-resorbable membrane. After four months, cone-beam computed tomography (CBCT) and intraoral scanner were used to measure dimensional changes of bone and soft tissue surface. Bone core specimens were harvested for histological analysis during implant osteotomy. Implant stability was assessed using a modified damping capacity analysis. Results: At four months postoperatively, dimensional changes in soft tissue surface resorption were less in the test group than in the control group; however, alveolar bone resorption was the same in both groups. Histological analysis revealed new bone formation, residual graft and fibrous connective tissue in both groups. The average primary implant stability (IST) value for both groups was approximately 70. There was no statistically significant difference in all parameters between two groups (p > 0.05). Conclusion: 3DP HA could potentially be used as an alternative bone graft material for alveolar ridge preservation.